Experience of work of community outreach teams for the protection of mental health in the sphere of assistance to patients with post-schizospheric depression - Stakhanov, Kiril (Psychiatry, Neurology and Medical Psychology, 2018)
The article describes the results of their own research and the experience of using the model of the work of social outreach teams for the protection of mental health within the framework of complex medical and psychological support for patients with post-schizophrenic depression. The study was conducted during 2011–2017 on the basis of the CI «Odesa Regional Medical Center of Mental Health». Methods of research were: theoretical, socio-demographic, clinical-psychopathological, psychodiagnostic, catamnestic, statistical. The study involved 141 patients for post-schizophrenic depression, who were provided on an outpatient basis with specialized medical and psychosocial care at home and in the community’s community. According to the results of the study, it is established that the implemented author medico-psychological support is effective and allows achieving significant improvement in the social functioning of patients with post-schizophrenic depression, improving the indicators of the psychoemotional and cognitivesphere, and significantly improving the quality of life of patients